PEDICLED MUSCLE FLAPS FOR THE MANAGEMENT OF IMPLANT COMPLICATIONS IN THE LOWER LIMBS:A REPORT - Alhotan Saleh (Sanamed)
Introduction: Metallic implants are widely used for the reconstruction of bony defects caused by fractures, excision of cancer, and degenerative bone disorders. These implants are associated with complications, including exposure and infection, particularly when vascularized tissue is needed for reconstruction. A key tool in plastic surgery to address these complications is the pedicled muscle flap. Case Report: This article presents two cases in which pedicled medial gastrocnemius and peroneus brevis muscle flaps were successfully used to salvage the hardware and achieve effective wound coverage. Conclusion: Pedicled medial gastrocnemius and peroneus brevis muscle flaps are valuable options for covering complicated skin defects over exposed implants.